Analysis of antibiotic consumption in burn patients - Soleymanzadeh-Moghadam, Somayeh; Azimi, Leila; Amani, Laleh; Rastegar Lari, Aida; Alinejad, Faranak; Rastegar Lari, Abdolaziz (German Medical Science GMS Publishing House, 2015)
Infection control is very important in burn care units, because burn wound infection is one of the main causes of morbidity and mortality among burn patients. Thus, the appropriate prescription of antibiotics can be helpful, but unreasonable prescription can have detrimental consequences, including greater expenses to patients and community alike. The aim of this study was to determine the effect of antibiotic therapy on the emergence of antibiotic-resistant bacteria. 525 strains of and were isolated from 335 hospitalized burn patients. Antibiotic susceptibility tests were performed after identification the strains. The records of patients were audited to find the antibiotic used.The results indicated that is the most prevalent Gram-negative bacteria. Further, it showed a relation between abuse of antibiotics and emergence of antibiotic resistance. Control of resistance to antibiotics by appropriate prescription practices not only facilitates prevention of infection caused by multi-drug resistant (MDR) microorganisms, but it can also decrease the cost of treatment.